Innovation and Efficiency of Brick MSME Products to Realize the One Village One Product - Zahara, Vadilla Mutia; Suci, Stannia Cahaya (MOVE: Journal of Community Service and Engagement, 2024)
Small and Medium Enterprises (MSMEs) in Indonesia, especially in Sigedong Village, have a significant role in economic development and job creation. To improve innovation and efficiency of MSMEs, the One Village One Product (OVOP) program is implemented, with a focus on brick production. The innovations implemented involve the use of wood powder as an alternative raw material, which is expected to improve product quality, efficiency, and sustainability. The implementation method includes counseling, mentoring, and collaboration with wood producers. The results of these innovations show that the bricks produced are of better quality, higher efficiency, and more environmentally friendly, as well as supporting sustainable production practices. Follow-up recommendations include the adoption of innovative methods, collaboration with academia and government, and periodic monitoring to ensure the success of innovation.